2019
DOI: 10.1057/s41299-019-00078-w
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Reputation Matter? Role of Social Media in Consumer Intention to Purchase Innovative Food Product

Abstract: Does corporate reputation matter? Role of social media in consumer intention to purchase innovative food product. Corporate Reputation Review. pp. 1-20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 154 publications
(131 reference statements)
3
24
0
Order By: Relevance
“…Furthermore, this study found the evidence that in the cement industry in Indonesia, reputation is able to increase people's purchase intention. The same finding was also shown by Balakrishnan & Foroudi (2020;Qalati et al 2021;Javed et al 2020;Bianchi et al 2019). Although Kim & Oh (2020) found that in the fashion industry, especially sports fashion, the corporate reputation has a weaker impact than the sustainability level.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Furthermore, this study found the evidence that in the cement industry in Indonesia, reputation is able to increase people's purchase intention. The same finding was also shown by Balakrishnan & Foroudi (2020;Qalati et al 2021;Javed et al 2020;Bianchi et al 2019). Although Kim & Oh (2020) found that in the fashion industry, especially sports fashion, the corporate reputation has a weaker impact than the sustainability level.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, a number of new marketing methods have emerged such as viral marketing (Divya & Evanita, 2021), E-WOM (Cheng et al 2021) and others. Several previous literatures support the influence of reputation on purchase intention (Balakrishnan & Foroudi, 2020;Qalati et al, 2021;Javed et al, 2020;Bianchi et al, 2019). Kim & Oh (2020) found that in the fashion industry there are two variables that can increase purchase intention, namely sustainability level and brand reputation.…”
Section: Corporate Reputation On Purchase Intentionmentioning
confidence: 90%
See 3 more Smart Citations